2020
DOI: 10.1002/fld.4884
|View full text |Cite
|
Sign up to set email alerts
|

Development of an efficient wetting and drying treatment for shallow‐water modeling using the quadrature‐free Runge‐Kutta discontinuous Galerkin method

Abstract: SummaryTo develop a robust, well‐balanced and quadrature‐free Runge‐Kutta discontinuous Galerkin (RKDG) shallow water solver, we introduce an efficient wetting and drying (WD) treatment in this paper. The main feature of this WD treatment is the use of vertex‐based linear reconstructed solutions in transition (partially wet) regions and high‐order solutions in smooth wet areas. To preserve the positivity of water depth, we also propose a modified time step size with the quadrature‐free scheme. The advantages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…Finally, the method presented in this paper does not straightforwardly resolve we/dry areas in the multilayer shallow water flows. However, using ideas of wet/dry treatment developed in [30] for standard single-layer shallow water equations, it is possible to reconstruct an efficient wetting and drying treatment for two-dimensional multilayer shallow-water models using the Runge-Kutta discontinuous Galerkin method. Results on these techniques will be reported in future works.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the method presented in this paper does not straightforwardly resolve we/dry areas in the multilayer shallow water flows. However, using ideas of wet/dry treatment developed in [30] for standard single-layer shallow water equations, it is possible to reconstruct an efficient wetting and drying treatment for two-dimensional multilayer shallow-water models using the Runge-Kutta discontinuous Galerkin method. Results on these techniques will be reported in future works.…”
Section: Discussionmentioning
confidence: 99%
“…Note that a similar hydrostatic reconstruction to (30) has been implemented in [5] for single-layer shallow water equations. The intermediate solutions…”
Section: Well-balanced Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that once the water depth at any node is nonpositive at a time step, the reconstructed water depth will no longer be negative by using this method. After reconstruction, the semidry elements are further divided into two parts [41,42]: flood elements for η max ≤ z b,max and dam-break elements for η max > z b,max . Finally, the elements are classified into four types: wet elements, dry elements, flood elements, and dam-break elements.…”
Section: Wet-dry Nodes and Elementsmentioning
confidence: 99%
“…In this model, the horizontal diffusion is not calculated at the WD interface, considering that the effects seem to be minor. For the flood type, gravity g is set to zero to ignore the influence of hydrostatic pressure in the convection term and bottom topography term to guarantee a well-balanced property [42].…”
Section: Calculation Of Elements In the Modelmentioning
confidence: 99%